История одинокой жизни: Чайковский, Бородин / Нина Берберова - Берберова Нина Николаевна (АСТ, 2010)
Экземпляры: АБ (20120303) / Инвентарный номер: 40331zzzzz / Цена: 277.31 / Сис.шифр: 85.3 / Авт.знак: Б 48 / ГРНТИ: 18.41.09 / ББК: 85.3